2023
DOI: 10.25259/jnrp_8_2022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinico-radiological profile, optical coherence tomography parameters, and outcome in MOGAD and Neuromyelitis optica spectrum disorder subtypes: A prospective observational study

Abstract: Objectives: The objectives of the study were to compare the clinico-radiological profile, optical coherence tomography (OCT) parameters and outcome in Myelin Oligodendrocyte Glycoprotein-IgG-associated disorders (MOGAD) and Neuromyelitis Optica Spectrum disorder subtypes. Materials and Methods: This prospective study involved collection of data regarding neurological assessment, neuroimaging, cerebrospinal fluid analysis, OCT parameters, treatment and outcome. Disease severity and disability were assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Several prior studies have shown a lower N:T ratio in NMO compared with MS (i.e., 0.93 ± 0.35 vs 1.36 ± 0.43), largely due to predominant temporal thinning in MS vs. diffuse thinning in NMO. 17,18 It appears that N:T ratio could be higher on average in both MS-ON and MOG-ON compared with NMO-ON. Further higher-powered studies would need to be done to confirm this.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several prior studies have shown a lower N:T ratio in NMO compared with MS (i.e., 0.93 ± 0.35 vs 1.36 ± 0.43), largely due to predominant temporal thinning in MS vs. diffuse thinning in NMO. 17,18 It appears that N:T ratio could be higher on average in both MS-ON and MOG-ON compared with NMO-ON. Further higher-powered studies would need to be done to confirm this.…”
Section: Discussionmentioning
confidence: 98%
“…As seen in Table 1, 8 cases were included in the analysis (3 female, 5 male). Median age at disease onset was 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) years. All patients had a MOG titer of 1:100-1:1,000 and had ON as determined by inclusion criteria.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Тем не менее степень частичной атрофии ЗН, развивающейся в отдаленном периоде ОН, также может различаться в зависимости от конкретного демиелинизирующего заболевания. Оценивать толщину перипапиллярного СНВС и комплекса ГКС следует не ранее чем через 6 мес после перенесенного ОН, когда произошли все структурные изменения на уровне данных структур ЗН [12].…”
Section: Conclusion the Study Showed The Most Pronounced Structural A...unclassified
“…В связи с этим различается прогноз восстановления ОЗ пациентов с МОГАЗ с единственным эпизодом ОН и с ремиттирующим течением ОН. Конечная ОЗ у обследуемых нами пациентов подгруппы МОG-ОНр была значимо ниже по сравнению с показателями пациентов с единственным эпизодом МОG-ОН и не отличалась от таковой в группе AQP4-OН, что свидетельствует о необходимости своевременной профилактики обострений для снижения инвалидизации пациентов [12].…”
Section: Va In Demyelinating Onunclassified